Effects of Immediate Orthodontic and Orthopedic Forces on Peri-Miniscrew Bones: Histomorphologic and Histomorphometric Assessment in Dogs. (25th December 2012) - Rismanchian, Mansour; Raji, Sayed Hamid; Teimori Rik, Danesh; Mohammad Razavi, Sayed; Khalighinejad, Navid; Goroohi, Hossein; Badrian, Hamid
Abstract : Aim . The aim of this study was histomorphologic and histomorphometric evaluation of peri-screw bone after immediate orthodontic and orthopedic forces and comparing them with a control group. Materials and Methods . 18 dual-top miniscrews were inserted in the premolar region of three Iranian dogs. Screws were divided into three groups: (1) the first group undergoing immediate orthodontic force of 300 cN, (2) the second group undergoing immediate orthopedic force of 600 cN and (3) a control group. Screws were explanted with adequate amount of surrounding bone after three months. Bone-screw contact (BSC), percentage of lamellar bone, and percentage of woven bone were evaluated. Wilcoxon and Man Whitney tests were used to analyze the data using SPSS software ver. 15 (α = 0.05 ). Results . There was no significant difference among the groups in terms of bone-screw contact (P value = 0.42 ), percentage of lamellar bone (P value = 0.83 ), and percentage of woven bone (P value = 0.88 ). Conclusion . By applying orthodontic and orthopedic forces to mini-screws the quality of surrounding bone and osseointegration will not be affected. Clinical Significance . Application of force to mini-screws is helpful in orthodontic-screw therapies.